Lithium-Induced Nephrogenic Diabetes Insipidus Self-Treated With Beer Potomania and Masquerading as Shock: : A Case Report - Badal, Joyce (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF to see the formatted meeting abstract.